Endotyping of Chronic Rhinosinusitis With and Without Polyp Using Transcription Factor Analysis - Tantilipikorn, Pongsakorn; Sookrung, Nitat; Muangsomboon, Soranart; Lumyongsatien, Jate; Bedavanija, Anan; Suwanwech, Triphoom (Frontiers in Cellular and Infection Microbiology, 2018)
Inflammation of the nose and paranasal sinus or rhinosinusitis (RS) is a significant global health problem that is both very common and very costly to treat. Previous reports reveal variability in histology and mechanism of inflammation in patients with chronic rhinosinusitis with and without polyp (CRScNP and CRSsNP, respectively). There are various methods and hypothesis that try to explain this variability. Accordingly, the aim of this study was to investigate the incidence of each type of sinonasal inflammation among patients diagnosed with CRScNP or CRSsNP using transcription factor analysis (TFA). This study included mucosa specimens from nose/paranasal sinuses from patients with chronic rhinitis (CR), CRSsNP, or CRScNP that were obtained at the Department of Otorhinolaryngology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand during the June 2009 to May 2012 study period. TFA was employed to measure the following transcription factors: T-box transcription factor (T-bet) for Th1, GATA binding protein 3 (GATA-3) for Th2, retinoic acid-related orphan receptor C (RORC) for Th17, and forkhead box P3 (FOXP3) for Treg. Forty-one subjects (22 males, 19 females) were enrolled, with a mean age of 45.93 ± 13 years. Twenty-six patients were diagnosed with CRScNP, 7 with CRSsNP, and 8 with CR (controls). The majority of CRScNP specimens (76.9%) had eosinophil count greater than 100 cells/high-power field (HPF). Mean eosinophil count was 930.08 ± 1,399 cells/HPF (range: 17–5,570). Th2 transcription factor (GATA-3) was statistically significantly higher in the CRScNP group than in the CRS and control groups (p < 0.001); whereas, Treg transcription factor (FOXP3) was statistically significantly lower in the CRScNP group than in the CRSsNP and control groups (p < 0.001). The transcription factors for Th1 and Th17 (T-bet and RORC, respectively) were not significantly different among the three groups. The result of transcription factor analysis revealed hyperfunction of Th2 in patients with CRScNP, which might result in hypereosinophilic infliltration in the polyps. One explanation for this finding is the decreased activity of Treg. Although environment-host interaction is the most probable hypothesis, the etiology of aberrant adaptive immunity needs to be elucidated.